Pendidikan Seksual dan Gender dalam Perspktif Parenting Islam - Masganti Sitorus; Dwi Nur Attira Ain; Nabila Nabila; Salsabila Wibowo (Badan Penerbit STIEPARI Press, 2026)
This study discusses sexual and gender education from the perspective of Islamic parenting, which plays a vital role in shaping children’s character, morality, and spiritual identity. The purpose of this research is to explore how Islamic values are integrated into the process of sexual and gender education within families, as well as to understand the role of parents as the primary educators based on the teachings of the Qur’an and Hadith. This research employs a qualitative method with a case study design, using in-depth interviews, participatory observation, and documentation analysis of Muslim families applying Islamic parenting principles. The findings reveal that Islamic-based sexual and gender education emphasizes the balance between knowledge, morality, and spirituality. Parents teach self-purity, modesty, social etiquette, and the principles of equality and justice between genders in a gradual and age-appropriate manner. The main challenges identified include low parental literacy regarding sexual and gender issues and the influence of digital media that often contradicts religious values. Nevertheless, Islamic parenting training and support from educational institutions and religious communities effectively enhance parents’ understanding and communication skills. In conclusion, sexual and gender education from an Islamic parenting perspective serves as a fundamental foundation for nurturing a generation that is physically and spiritually healthy, morally upright, and capable of interacting justly and ethically amidst modern challenges.